2009
DOI: 10.1021/jf900011f
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Antiproliferative Activities and Action Mechanisms of Extracts from Two Species of Ganoderma on Tumor Cell Lines

Abstract: The antiproliferative activities on tumoral cells, namely, human breast cancer (MCF-7 and MDA-MB-231), hepatoma (HepG2) and myeloid leukemia (HL-60), of ethanolic extracts from two species of Ganoderma, G. lucidum and G. sinense, were investigated. Though both extracts had certain antiproliferative activities, their chemical characteristics, including nucleosides, triterpenoids and sterols, were significantly different. Their effects on MDA-MB-231 cells were further studied using apoptotic detection and cell c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
38
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(41 citation statements)
references
References 30 publications
(33 reference statements)
2
38
1
Order By: Relevance
“…For example, extracts from medicinal mushrooms C versicolor and G lucidum, 27,28 medicinal herbs S barbata, A membranaceus, and C longa, [29][30][31] and nutritional compounds diindolylmethane and quercetin 32,33 induced apoptosis in breast cancer cells, respectively. Nevertheless, the cytotoxic activities of some isolated extracts were achieved at higher concentrations with IC 50 in the range of 72 to 514 µg/mL for MDA-MB-231 cells, 27,28 whereas BD demonstrated cytostatic effect for the same cell line at markedly lower concentrations with IC 50 22 µg/mL. Therefore, the combination of different compounds in BD can increase the biological activity of particular compound at lower dose, and instead of cytotoxic effect can cause cytostatic cell cycle arrest.…”
Section: Discussionmentioning
confidence: 99%
“…For example, extracts from medicinal mushrooms C versicolor and G lucidum, 27,28 medicinal herbs S barbata, A membranaceus, and C longa, [29][30][31] and nutritional compounds diindolylmethane and quercetin 32,33 induced apoptosis in breast cancer cells, respectively. Nevertheless, the cytotoxic activities of some isolated extracts were achieved at higher concentrations with IC 50 in the range of 72 to 514 µg/mL for MDA-MB-231 cells, 27,28 whereas BD demonstrated cytostatic effect for the same cell line at markedly lower concentrations with IC 50 22 µg/mL. Therefore, the combination of different compounds in BD can increase the biological activity of particular compound at lower dose, and instead of cytotoxic effect can cause cytostatic cell cycle arrest.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, in a thorough and detailed review, Paterson (12) investigated the antiproliferative effects on tumorigenic cells and the protein chemical characteristics of WS and HMC extracts from three species of Reishi (R, 2R and A2R). The effects of G. lucidum extracts on tumorigenesis and metastasis in a cultured human tumor cell line have also been examined (13)(14)(15)(16)(17). In the present study, WS and HMC fractions prepared from three species of Reishi (each sample 5 g dry weight) were examined ( Table I).…”
Section: Discussionmentioning
confidence: 99%
“…Studies of Liu et al (2009) concluded ethanol extracts of G. sinense responsible for activities on human breast cancer, hepatoma and myeloid leukemia, anti-proliferation effect through apoptosis pathway and cell cycle arrest effect. Ganoderma sinense have anti-tumoral proliferation effect through both apoptosis pathway and cell cycle arrest effect, and some other compounds such as sterols and/or nucleosides may contribute to their activity besides triterpenoids.…”
Section: Ganoderma Sinensementioning
confidence: 99%